(untitled) (Scientific Journal of the Dragomanov Ukrainian State University Series 2 Computer-Oriented Learning Systems, 2024)
The article is devoted to analyzing the effectiveness of using web-oriented server management systems in training information technology specialists. The purpose of this study is to explore the effectiveness of using web-oriented server management systems in the process of training information technology specialists. Web-oriented server management systems are powerful tools that simplify servers and hosting administration. With the help of these systems, the user is provided with a graphical interface for managing various aspects of the server, including websites, databases, e-mail, etc. The rapid development of web technologies requires modern information technology specialists to have in-depth knowledge of web server administration. Using web-based server management systems, such as Ajenti, Webmin, Sentora, VestaCP, CentOS Web Panel, Kloxo-MR, Froxlor, ISPConfig, and others, provides powerful website management tools. Based on theoretical analysis and practical research, it was found that using such systems contributes to the formation of students’ practical skills, increasing their motivation to study and a deeper understanding of the principles of operation of modern infrastructures of organizations using information technologies. Using web-based server management systems in the educational process makes it more effective and engaging for students. This contributes to the development of practical skills, increasing motivation, and better training of specialists who are ready to work in modern companies in the field of information technologies. Using web-based server management systems in the course "Web-based educational computer systems" has several advantages. They allow students to gain practical server administration skills, increase learning efficiency, and contribute to developing interest in information technologies. The results obtained can be used to optimize curricula and improve the quality of training of information technology specialists.